Features of the relationship between the chemical composition of cow’s milk and its freezing point values - Korkh, Igor; Rusko Nаtaliia; Paliy, Anatoliy; Boiko, Nataliia; Admin, Oleksandr; Pavlichenko, Olena; Kudriashov, Andriy; Karban, Yuliia; Palii, Nataliya (Problems of Cryobiology and Cryomedicine, 2026)
This article reveals the seasonal characteristics of the formation of the most significant factors that affect the freezing point of cow’s milk. The results of the generalization performed in this study on the relationship between the freezing point of milk and the content of its main components, which determine its nutritional value, can provide a significant foundation for developing organizational mechanisms to regulate milk production and implement a unified quality policy at all management levels through mathematical modeling. The chosen approach enables the ranking of basic milk quality properties, ensuring the selection of the most important ones. It has been established that an increase in the mass fraction of dry matter and lactose in milk leads to a corresponding decrease in its freezing point. Furthermore, it has been substantiated that the freezing point of milk varies throughout the year. Considering these values, we can fairly assess the degree to which milk has been adulterated with water while ensuring its high quality and safety. Probl Cryobiol Cryomed. 2025; 35(3): 130—137